2017
DOI: 10.1007/jhep09(2017)100
|View full text |Cite
|
Sign up to set email alerts
|

Bell’s inequality and entanglement in qubits

Abstract: Abstract:We propose an alternative evaluation of quantum entanglement by measuring the maximum violation of the Bell's inequality without information of the reduced density matrix of a system. This proposal is demonstrated by bridging the maximum violation of the Bell's inequality and a concurrence of a pure state in an n-qubit system, in which one subsystem only contains one qubit and the state is a linear combination of two product states. We apply this relation to the ground states of four qubits in the Wen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 20 publications
0
20
0
Order By: Relevance
“…Hence Quantum Entanglement cannot be a source of violation for Mermin's inequality. Choosing other operators can show the monotonically increasing behavior in the GHZ class [7,8]. However, the proposal is also not general.…”
Section: Experiments Correlator and Tripartite Entanglementmentioning
confidence: 98%
See 1 more Smart Citation
“…Hence Quantum Entanglement cannot be a source of violation for Mermin's inequality. Choosing other operators can show the monotonically increasing behavior in the GHZ class [7,8]. However, the proposal is also not general.…”
Section: Experiments Correlator and Tripartite Entanglementmentioning
confidence: 98%
“…In other words, the 2-qubit state is too unusual. It is hard to extend the relationship to a general n-qubit state [7,8]. Indeed, various difficulties of many-body Quantum Entanglement already appear in the 3-qubit state.…”
Section: Introductionmentioning
confidence: 99%
“…We use seven-qubit quantum states as an example to estimate intensity of quantum entanglement in the maximally entangled state through Bell's inequality [11,18]. A ground state of a toric code model [3,4] on a disk manifold can be shown to have local maximum quantum entanglement in our quantum states through an upper bound of Bell's inequality [9,14,17]. We also discuss relations between an upper bound of Bell's inequality and concurrences of pure states of a region [13].…”
Section: Maximally Entangled State and Bell's Inequalitymentioning
confidence: 99%
“…A ), and the entanglement entropy of the region A, S A , through the two maximal eigenvalues of the 3 × 3 Rmatrix R ij ≡ Tr(ρσ i ⊗ σ j ) [14,15], where i = 1, 2, 3 and j = 1, 2, 3, and σ x , σ y , σ z are the Pauli matrices defined in [16]. For some n-qubit quantum states, an upper bound of Bell's inequality is also a monotonic function with respect to the generalized concurrence of the pure state of a region A [9,17], C A (m, ψ) ≡ 2(1 − 2 m−1 Tr A ρ 2 A ), and the entanglement entropy of the region A through the generalized R-matrix [9,17], R i 1 i 2 ···in ≡ Tr(ρσ i 1 ⊗ σ i 2 ⊗ · · · ⊗ σ in ) ≡ R Iin , where i α = x, y, z and α = 1, 2, · · · , n are the site indices. The generalized R-matrix can be rewritten as a 3 n−1 × 3 matrix R Iin with the first index being a multi-index I = i 1 i 2 · · · i n−1 and the second index being i n .…”
Section: Introductionmentioning
confidence: 99%
“…In [20], Horodecki et al showed that for arbitrary mixed two-qubit state the maximal violation of CHSH inequalities is related to the eigenvalues of correlation matrix, and derived a necessary and sufficient condition for violating the inequalities accordingly. Based on this idea, the authors [21] generalize the the the maximal violation of the Bell's inequality in a nqubit system by using the unfolded matrix of correlation tensor. It should be noted that this generalization is direct.…”
Section: Introductionmentioning
confidence: 99%